Biomimetic Diselenide‐Bridged Mesoporous Organosilica Nanoparticles as an X‐ray‐Responsive Biodegradable Carrier for Chemo‐Immunotherapy. Issue 50 (9th November 2020) - Shao, Dan; Zhang, Fan; Chen, Fangman; Zheng, Xiao; Hu, Hanze; Yang, Chao; Tu, Zhaoxu; Wang, Zheng; Chang, Zhimin; Lu, Junna; Li, Tianyu; Zhang, Yuan; et al.
Abstract: Chemotherapy causes off‐target toxicity and is often ineffective against solid tumors. Targeted and on‐demand release of chemotherapeutics remains a challenge. Here, cancer‐cell‐membrane‐coated mesoporous organosilica nanoparticles (MONs) containing X‐ray‐ and reactive oxygen species (ROS)‐responsive diselenide bonds for controlled release of doxorubicin (DOX) at tumor sites are developed. DOX‐loaded MONs coated with 4T1 breast cancer cell membranes (CM@MON@DOX) show greater accumulation at tumor sites and prolonged blood circulation time versus an uncoated control in mice bearing 4T1 orthotopic mammary tumors. Under low‐dose X‐ray radiation, the DOX‐loaded MONs exhibit carrier degradation‐controlled release via cleavage of diselenide bonds, resulting in DOX‐mediated immunogenic cell death at the tumor site. Combination with a PD‐L1 checkpoint blockade further enhances inhibition of tumor growth and metastasis with low systemic toxicity. Together, the findings show the promise of these biomimetic, radiation‐responsive diselenide‐bond‐bridged MONs in chemo‐immunotherapy. Abstract : Biomimetic mesoporous organosilica nanoparticles are tailored for radiation‐responsive delivery of doxorubicin to solid tumors and are combined with a PD‐L1 checkpoint blockade as a chemo‐immunotherapy strategy. Under low‐dose X‐ray radiation, these cancer‐cell‐membrane‐coated nanotherapeutics exhibit degradation‐controlled drug release and induce anti‐tumor immune responses, leading to enhanced tumor regression and metastasis inhibition with low systemic toxicity when combined with anti‐PD‐L1.